A novel production route and process optimization of biomass-derived paraffin wax for pharmaceutical application. (1st December 2020) - Gruber, Hannes; Lindner, Lukas; Arlt, Stefan; Reichhold, Alexander; Rauch, Reinhard; Weber, Gerald; Trimbach, Jürgen; Hofbauer, Hermann
Abstract: The Biomass to Liquid (BtL) Fischer-Tropsch (FT) route converts lignocellulosic feedstock to renewable hydrocarbons. This, paper shows a novel production route for biomass-derived synthetic paraffin wax via gasification of lignocellulosic feedstock, Fischer-Tropsch synthesis (FTS) and hydrofining. The Fischer-Tropsch wax was fractionated, refined and analyzed with respect to compliance to commercial standards. The fractioned paraffin waxes were hydrofined using a commercial sulfide NiMo–Al2 O3 catalyst and a trickle bed reactor. A parametric variation was performed to optimize the hydrofining process. It was shown that the produced medium-melt paraffin wax could fulfill the requirements for "Paraffinum solidum" defined by the European Pharmacopoeia (Ph. Eur). The high-melt wax fraction showed potential to be used as food packaging additive. Furthermore, the renewable wax was analyzed regarding PAH content and it was shown that the hydrofined wax was quasi-PAH-free. Graphical abstract: Image 1 Highlights: A novel route to produce renewable synthetic paraffin wax was shown. A parametric variation for the hydrofining process was performed. A renewable wax that complied with the Ph. Eur. standard was produced. A long-term test run indicated stable production quality. The renewable synthetic paraffin waxes were quasi-PAH-free.